Cumplimiento de los principios de celeridad y agilidad en el trámite de visto bueno señalado en el art. 621 del código del trabajo - Villacís Jiménez, Willan Alecsander (2017)
The approval is a mechanism established by the Labour Code, in which one of the parties, both employer and worker may terminate the employment relationship, for the reasons set out in Art. 172 and 173 of the same code respectively. Art. 621 of the Labour Code establishes the procedure for approval, with the labor inspector who carries it out, which received the application, notify the applicant within twenty four hours, giving him two days to answer. With the answer or in absentia, proceed to investigate the merits of the application and issue its decision within three days, granting or denying approval. The resolution shall include the information and reasons on which it is based. But the fact is that these terms and time regarding the procedure are not very clear, respected and carried out by the Labour Inspector, since he knows the labor inspector, even when issued Resolution granting or not the approval, so that the administrative process becomes too slow, and also prevails written system, so it goes against the principles of the administration of justice, that the substantiation of the processes in all matters, instances, stages and proceedings will be out by the oral system, also affecting the principles of simplification, uniformity, efficiency, speed and procedural economy. The administrative process of approval is a procedure to expedite the drawbacks of the relations between employers and workers, and the decongestion of the judicial function, but even administrative be followed by rules and principles of the administration of justice and the lack of simplification of compliance with the terms for solving the process of seen, the regulation of this legal institution is necessary, in that orality, speed and procedural economy, the labor inspector must process the application Viewed Good, impartiality, thoroughness, neatness and a human sense, prior to its decision to terminate the Individual Work Contract. It concludes that the processing of Viewed Good duly demonstrating at the stage of research transgression of one or more grounds prescribed in the Labour Code, is feasible from a legitimate point of view of any of the parties involved , ie employers or workers, but in the end the worker to administrative due process committed by the Labour Authority specifically against the wording right, run out of his job and worse if there is pressure or any violation is irresponsible, because other institutions of labor law, which similarly guarantee the human rights of workers, as the untimely dismissal and eviction therefore all areas of the working class would be leaving defenseless as rules dealing of these institutes in some of its parts are obsolete or misapplied. Hence it should create a reform that regularizes the correct application of the method of application Viewed Good, cause agility and safety and validity procedural, but after all come to the conclusion that the legal institution of Viewed Good , is a administrative procedure later if you feel affected in their right especially the worker, could follow a judicial process. For these and other considerations, the processing of Viewed Good, should solve in the allotted time the problems raised by the worker and the employer in labor relations, so that should receive it from the field of law, in the time we have already mentioned and you should limber up in processing without violating the rights and obligations of the parties, always ensuring job security worker, as the weaker party in the employment relationship. However until this is possible if it is important to create a reform term as already stated, so then we registered a draft rule governing the proceedings and the maximum time that should last, the application Viewed Good as one of the grounds for terminating the employment relationship in an employment contract.